Elaboração de um plano de manutenção preventiva para a indústria metal mecânica - Rissi, Leonardo (2023)
In a scenario where the economy is increasingly globalized, new challenges arise for industries, one of them is the ability to serve their customers in an agile way, however maintaining the quality of the product is even more important, in view of this context, we do if it is necessary to have more modern machines every day, the activity of industrial maintenance has been gaining an important role, becoming a strategic and fundamental function so that industries do not stop their activities. Therefore, the present work aims to seek a theoretical foundation on maintenance, with emphasis on preventive maintenance, in order to be able to apply the concepts in a metalworking industry. In this sense, the maintenance plan is formed and applied, focusing on the cutting and folding sector, aimed at the laser cutting machine, since it is considered a bottleneck for the industry in question, thus seeking to reduce costs, increase productivity through prevention. To formulate this maintenance plan, the failure mode and effect analysis tool (FMEA) is applied, with which it is possible to define the risk level for each component. Through Pareto it is possible to highlight the most critical components, and identify the points that record the greatest loss of time, with unnecessary stops. Through the results obtained, it is concluded that the company has a deficiency in identifying critical points. Thus, the maintenance plan created in this article was able to demonstrate the most flawed items, and with that, it is expected that new processes are implemented and followed, in order to guarantee reliability for the equipment and for management.